Natural Products and Derivatives in Human Disorders - Rufino-Palomares, Eva E.; Lupiáñez, José Antonio (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
With this Special Issue, we have aimed to collect, publish and disseminate some of the most significant and recent contributions using both natural compounds present in living organisms and some of their chemical derivatives aimed at reducing the risk of developing inflammatory and oxidative diseases such as cancer, metabolic syndrome and other human disorders related to the bone, vascular and ocular systems. The publication of articles on the anticancer and antioxidant activity of natural compounds and their derivatives is particularly encouraged.Natural products, many of them phytochemicals, are bioactive compounds. They have traditionally been used by different cultures for the prevention and treatment of various human diseases. Subsequently, their chemical derivatives are being used to enhance their bioactivities. antiproliferative, antitumour, growth stimulating, as well as cardio- and neuroprotective activities, with particular attention being paid to the study of their antitumour capacity, through potential modulation of cancer initiation and growth, cell differentiation, apoptosis and autophagy, angiogenesis and metastatic dissemination.Aucuba japonica; aucubin; cornea; dry eye; tear; chondrosarcoma cells; osteoarthritis; Ryupunghwan (natural product mixture); IL-1β; isomucronulatol 7-O-β-d-glucoside; ecliptasaponin A; cardiomyocytes (H9C2 cells); angiotensin II; hypertension; No-ap (natural product mixture); reactive oxygen species; roseoside; icariside E4; acetylcholinesterase; butyrylcholinesterase; triterpenoids; Teucrium mascatense; natural plant products; anticancer activity; breast and cervical cancer; apoptosis; caspases; aberrant crypt foci; colon cancer; mucin depleted foci; maslinic acid; dimethylhydrazine; saikosaponin d; neuropilin-1; HepG2; metabolomics; metabolite deregulation score; n/a